2007
DOI: 10.1136/bjo.2006.101121
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor and its receptors in rosacea

Abstract: Expression of VEGF receptors, both by vascular endothelium and infiltrating mononuclear cells, is observed in rosacea. Although not expressed by endothelium, VEGF is present in epidermis and epithelium, and is expressed by infiltrating cells. VEGF receptor-ligand binding may contribute to the vascular changes and cellular infiltration that occurs in rosacea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 20 publications
2
39
0
5
Order By: Relevance
“…Angiogenesis induced by cathelicidin is mediated by an increase in vascular endothelial growth factor (VEGF) in epidermal keratinocytes, and could represent an explanation for these vascular events in rosacea (25) . An increase in expression of VEGF and its receptors was demonstrated in the skin of patients with rosacea (35,36) .…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…Angiogenesis induced by cathelicidin is mediated by an increase in vascular endothelial growth factor (VEGF) in epidermal keratinocytes, and could represent an explanation for these vascular events in rosacea (25) . An increase in expression of VEGF and its receptors was demonstrated in the skin of patients with rosacea (35,36) .…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…15 Despite these mediators having been identified, the primary initiating mechanism for inflammation is still not clear.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Immunohistochemistry revealed increased VEGF expression in lesional versus nonlesional skin of rosacea patients. 128 Smith et al 129 showed expression of both VEGFR1 and 2 in rosacea vascular endothelium and infiltrating mononuclear cells.…”
Section: Hemangioendotheliomas Key Point D Antiangiogenic Treatment Hmentioning
confidence: 99%